Methods of Analyzing Judges' Decisions in Normative Legal Research Case-based Approach and Islamic Law - Sukiati, Sukiati; Mukhsin, Abd.; Al-Farizi, Dava (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study aims to examine how decision analysis studies should be conducted. In addition to examining the case approach in normative legal research, which is a commonly used approach in decision analysis studies, this study was also conducted to investigate the methods and characteristics of decision analysis. Using qualitative and document research methods, data was collected through focus group discussions and documentation. This study found that decision analysis research is specifically a case-specific study, possibly using philosophical and conceptual approaches simultaneously. The steps of decision analysis research also specifically follow the IRAC (Issue, Rule, Attention and Conclusion) method. This study is expected to contribute to the development of the discourse on legal research methodology with its various approaches, especially approaches that have been introduced in normative legal research. Practically, this study is expected to provide guidance for students to conduct normative legal research with a case approach, especially in decision analysis research. The results of this study are also expected to be a guide for supervisors to guide students who conduct normative legal research with a case approach, especially research on the analysis of judges' decisions.